Gastrointestinal Amyloidosis: Diagnostic Approach and Treatment - Catarina Budyono; Achmad Fauzi; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Amyloidosis is a disease marked by deposition of misfolded proteins, known as amyloids, in the extracellular space, including gastrointestinal tract. According to the precursor protein, amyloidosis is classified into six types; all of which can be involved in the gastrointestinal tract. Amyloidosis has weight loss and gastrointestinal bleeding as the most frequent symptoms. Gastrointestinal tract biopsy is diagnostic in most cases of amyloidosis and Congo red stain is used to confirm the amyloid proteins deposit. Treatment of amyloidosis consists of controlling symptoms, terminating protein formation and deposit, and treating the underlying diseases. Chemotherapy might be applied depends on the type of amyloidosis.